(untitled) - Cushner, Kenneth (New York, 2012)
Human Diversity in Education is designed to prepare teachers for the wide diversity of students that they are certain to encounter in their classrooms, schools, and communities.
Keywords: Giáo dục đa văn hóa,Multicultural education; Hoa Kỳ,United states